On the construction of the series solution of the Adomian decomposition method - Gabriel, Bissanga; Francis, Bassono; Pare, Youssouf; Some, Blaise (International Journal of Applied Mathematical Research, 2013)
In this paper, the Adomian decomposition methodis used to construct the solution of integral equa-tions and the choice of the ?rst term of the se-ries solution in the algorithme of Adomian isdi¤erent of the usual one.